KEMAMPUAN MENULIS PETUNJUK SISWA KELAS VIII SMP NEGERI 5 BANDARLAMPUNG TAHUN AJARAN 2011/2012 - santi noviyana; muhammad fuad; mulyanto widodo (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
The students’ ability in writing instructions at the eight grade of SMP Negeri 5 Bandarlampung 2011/2012 period is discussed as the problem. This research aims to describe the students’ ability in writing instructions at the eight grade of SMP Negeri 5 Bandarlampung 2011/2012 period. This research uses descriptive method. Writing test was adminstered through giving writing instruction activity as the technique in collecting in data. There are some aspects considered in scoring systems: clarity, the order of instructions, sentence effectiveness, spelling and atrractiveness. The populations of this research was 203 students from six classes by 30 students as the sample or 15% of population.Based on the result, it can be said the students’ ability in writing instructions at the eight grade of SMP Negeri 5 Bandarlampung 2011/2012 peroide is categorized good. It can be seen on the average mastery by 71.13. For each indicator clarity by 80,67 is catagorized good. The order of instructions by 82,3 is categorized good. The sentence effectiveness by 68,33 is categorized fair. Spelling by 47,67 is categorized low. And attractiveness by 83,33 is categorized good. Keywords: instructions, The students’ ability in writing